Risk assessment of power systems : models, methods, and applications - Li, Wenyuan, 1946- (Hoboken, New Jersey : IEEE Press, Wiley, 2014)
"Risk Assessment of Power Systems addresses the regulations and functions of risk assessment with regard to its relevance in system planning, maintenance, and asset management. Brimming with practical examples, this edition introduces the latest risk information on renewable resources, the smart grid, voltage stability assessment, and fuzzy risk evaluation. It is a comprehensive reference of a highly pertinent topic for engineers, managers, and upper-level students who seek examples of risk theory applications in the workplace"--
"This book discusses the models, methods and applications of risk assessment in physical power systems with a focus on various application problems"--
9.4 Example 1: Selecting Substation Configuration9.5 Example 2: Evaluating Effects of Substation Configuration Changes; 9.6 Example 3: Selecting Transmission Line Arrangement Associated with Substations; 9.7 Conclusions; 10: Application of Risk Evaluation to Renewable Energy Systems; 10.1 Introduction; 10.2 Risk Evaluation of Wind Turbine Power Converter System (WTPCS); 10.3 Risk Evaluation of Photovoltaic Power Systems; 10.4 Conclusions; 11: Application of Risk Evaluation to Composite Systems with Renewable Sources; 11.1 Introduction
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Electric power systems -- Reliability -- Mathematical models; Electric power failures -- Risk assessment; Monte Carlo method; TECHNOLOGY & ENGINEERING / Electrical; Electronic books; Electronic books